ANALISIS KEBIJAKAN SUBSIDI PENDIDIKAN BAGI MASYARAKAT BERPENGHASILAN RENDAH - Meilani Bekti Hartanti; Septi Puji Astuti; Sutrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the implementation and impact of education subsidy policies for low-income communities in an effort to increase equitable access to education. The method used is a qualitative approach with a literature study type of research, which utilizes various sources such as scientific journals, books, government reports and relevant policy documents. Data were analyzed descriptively through a process of assessment, grouping and interpretation to obtain a comprehensive picture. The research results show that the education subsidy policy in Indonesia has been implemented through various programs, such as School Operational Assistance (BOS), Smart Indonesia Card (KIP), scholarship programs, and higher education subsidies, which in general are able to increase access to education for low-income people. This is characterized by increasing school enrollment rates and decreasing school dropout rates. However, policy effectiveness still faces a number of obstacles, including inaccurate targeting of aid recipients, uneven distribution, and weak monitoring and data collection systems. In addition, the impact of policy is more dominant in increasing access rather than quality of education. Therefore, improvements are needed in the implementation aspect so that education subsidy policies can run more optimally and sustainably.